The preserving of urban environment from the pollution of small and medium industries in desert cities: the case of the urban agglomeration of souf, Algeria - Lemehannet, Ali; Benmissi, Ahcene (Journal of Human Sciences, 2021)
This study is treating the subject of protecting the urban environment from the pollution caused by small and medium industries, which most third world cities suffer from, such as Algeria, in this research we touch on the oasis cities, taking the cities of assembly urban of souf as an example. This study starts from determining the causes of pollution to the urban environment, and that is during the increase number of small and medium industries enterprises, as we find some of them inside residential quarters, and some inside industrial areas bat its planning in a random way, and it was not separated from residential quarters to protect the urban environment from pollution, then we proposed solutions to this problem, by transferring all industrial establishments from residential quarters to industrial areas, and re-planning these areas, and setting up natural barriers of palm and fruit trees between industrial areas and residential quarters.